Coating μm TPB on a cylindrical detector and studying the sample films being cooled to LN and LHe temperatures. (1st December 2022) - Zhou, Jiangfeng; Ouyang, Zebang; Liao, Junhui; Liang, Zhuo; Peng, Zhaohua; Zhang, Lei; Zhang, Lifeng; Zheng, Jian; ,
Abstract: ALETHEIA is a newly established dark matter direct detection project that aims at hunting for low-mass WIMPs. TPB is widely implemented in liquid helium and argon experiments to shift VUV photons to visible light. We first report that we have successfully coated ∼ 3 μm TPB on the inner walls of a 10-cm cylindrical PTFE detector; we split the coating process into two steps to have all of the surfaces being coated with the same thickness; three independent methods were applied to figure out the thickness of the TPB coating layers, and consistent results were obtained. Second, with an SEM machine, we scanned the surface of TPB coating sample films exposed to different cryogenic temperatures. The first group of sample layers were immersed into a liquid nitrogen dewar for forty hours, the second group samples were cooled to 4.5 K for three hours, and the third group stayed at room temperature after coating. The SEM-scanned images of the sample films barely show any noticeable difference.